Physiopunk Vol. 1 Speculative fiction for future physiotherapies - Maric (PhD), Filip; Nikolaisen, Liv Johanne; Bårdsen, Åse (OpenPhysio Journal, 2021)
In light of today’s deeply connected social and environmental crises, environmental and sustainability education is increasingly being integrated into public health and healthcare professional education around the world (Barna, Maric, Simons, Kumar & Blankestijn, 2020). The Norwegian ‘regulations on national guidelines for physiotherapist education’ clearly support the integration of these topics by stating that ‘in addition to individually oriented work, physiotherapists should contribute to improving public health and the sustainability of society on the group and system-levels…with competencies in interdisciplinary and goal-oriented collaborations within the health- and care-sector and other sectors…to meet societies existing and future needs’ (Forskrift om nasjonal retningslinje for fysioterapeututdanning, 2019, our translation). In a new introductory public health module for our 1st year physiotherapy students at UiT Norges arktiske universitet we therefore integrated education about the social and environmental problems of our time and how they interact with health at many levels to inspire students to imagine novel futures for physiotherapy and the role of healthcare professionals in the future.